2019
DOI: 10.1002/mame.201970033
|View full text |Cite
|
Sign up to set email alerts
|

Natural Silk Film for Magnesium Protection: Hydrophobic/Hydrophilic Interaction and Self‐Healing Effect

Abstract: Front Cover: In article number 1900412 by Ekaterina V. Skorb, Elena F. Krivoshapkina, and co‐workers, magnesium implants sonochemically treated in silk solution demonstrate significant improvement of corrosion resistance compared to control samples sonochemically treated in water. The deposition of a silk layer enhances the obtained corrosion resistance by 18 times, resulting in a 54‐fold increase overall. Thus, hybrid effects of sonochemical oxidative protection combined with silk assembly is promising for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Another highly promising material which is biocompatible, provides high mechanical strength and has a unique structure is spider silk [ 94 96 ]. Zhang et al [ 97 ] have demonstrated the potential of a TENG based on recombinant spider silk.…”
Section: Natural Materialsmentioning
confidence: 99%
“…Another highly promising material which is biocompatible, provides high mechanical strength and has a unique structure is spider silk [ 94 96 ]. Zhang et al [ 97 ] have demonstrated the potential of a TENG based on recombinant spider silk.…”
Section: Natural Materialsmentioning
confidence: 99%
“…According to the World Corrosion Organization (WCO), the global annual cost of corrosion is approximately 3.1%–3.5% of a country's gross domestic product (GDP) 1 . The situation is more critical when the metallic structures are used as implants since they are expected to have a longer lifespan as well as enhanced biocompatibility 2–4 . For example, 316 L stainless steel (SS) has been considerably employed as a temporary implant, however, the release of ions including chromium, nickel, and molybdenum creates concerns during the use of 316 L SS in the human body 5–7 .…”
Section: Introductionmentioning
confidence: 99%